Chikungunya infection in Malaysia: Comparison with dengue infection in adults and predictors of persistent arthralgia - Zim, M.A.M.; Sam, I.C.; Omar, S.F.S.; Chan, Y.F.; AbuBakar, Sazaly; Kamarulzaman, A. (2013)
Background: Chikungunya virus (CHIKV) and dengue virus (DENV) co-circulate in areas endemic with the Aedes mosquito vectors. Both viruses cause similar illnesses which may be difficult to distinguish clinically. CHIKV is also associated with persistent arthralgia. Objectives: To compare and describe factors which differentiate between DENV and CHIKV infections on presentation; and to describe predictors of persistent arthralgia in CHIKV patients. Study design: Patients aged > 14 years diagnosed with acute CHIKV and DENV infections in Kuala Lumpur, Malaysia were retrospectively identified. Clinical and laboratory data were obtained from medical records, and compared. CHIKV patients were telephoned 15-24 months later and interviewed about persistent symptoms. Logistic regression analysis was performed. Results: A total of 53 CHIKV and 113 DENV patients were included. CHIKV patients were older and more likely to be female. CHIKV was independently associated with arthralgia and rash, while DENV was associated with myalgia, raised aspartate transaminase, and leucopaenia. Forty CHIKV patients were followed up, with a median duration of self-reported arthralgia of 3 months (range, 0-24 months). Eighteen (45) had persistent arthralgia beyond 4 months, for which age > 40 years was an independent predictor. At 1 year, 9 (22.5) patients had arthralgia. Conclusion: In Kuala Lumpur, selected clinical and laboratory predictors help to distinguish between DENV and CHIKV infections. Persistent arthralgia was a frequent sequel of CHIKV infection in this cohort. (C) 2012 Elsevier B. V. All rights reserved.